Creative trans-border cooperation in the field of operations research and sustainable development in civil engineering - Kapliński, Oleg; Vilutienė, Tatjana (Technological and Economic Development of Economy, 2021)
The paper presents an overview of the history and achievements of trans-border cooperation in the Lithuania-Germany-Poland triangle in planning instruments in Construction Management, decision-making theory, application of Operational Research, and Multiple Criteria Decision Making (MCDM) methods in Civil Engineering and sustainable development. The cooperation and results of the Colloquiums with 35 years of tradition, their multidimensional nature is underlined. The research instruments, methods, studied phenomena are reviewed and characteristic applications in engineering and economics are presented. The knowledge and combined efforts of three academic centers have created a synergy which set in motion many original methods and spectacular implementations. The Colloquium calendar and the evolution of organizational forms are presented along with the inclusion of the informal EURO Working Group on Operations Research in Sustainable Development and Civil Engineering.